Review and the state of the art: Sol–gel and melt quenched bioactive glasses for tissue engineering. Issue 6 (9th June 2015) - Kaur, Gurbinder; Pickrell, Gary; Sriranganathan, Nammalwar; Kumar, Vishal; Homa, Daniel
Abstract: Biomaterial development is currently the most active research area in the field of biomedical engineering. The bioglasses possess immense potential for being the ideal biomaterials due to their high adaptiveness to the biological environment as well as tunable properties. Bioglasses like 45S5 has shown great clinical success over the past 10 years. The bioglasses like 45S5 were prepared using melt‐quenching techniques but recently porous bioactive glasses have been derived through sol–gel process. The synthesis route exhibits marked effect on the specific surface area, as well as degradability of the material. This article is an attempt to provide state of the art of the sol–gel and melt quenched bioactive bioglasses for tissue regeneration. Fabrication routes for bioglasses suitable for bone tissue engineering are highlighted and the effect of these fabrication techniques on the porosity, pore‐volume, mechanical properties, cytocompatibilty and especially apatite layer formation on the surface of bioglasses is analyzed in detail. Drug delivery capability of bioglasses is addressed shortly along with the bioactivity of mesoporous glasses. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1248–1275, 2016.